Agreement on Enhancing International Arctic Scientific Cooperation - Arctic Council (Arctic Council Secretariat, 2017)
Agreement on Enhancing International Arctic Scientific Cooperation, signed at the Fairbanks Ministerial meeting, 11 May, 2017. Agreement on Enhancing International Arctic Scientific Cooperation, signed at the Fairbanks Ministerial meeting, 11 May, 2017.